Clinical and pathophysiological foundations and advanced developments in the rehabilitation of patients after ischemic stroke - E. G. Demianovskaia; A. S. Vasiliev (Лечащий Врач, 2021)
In cerebral infarction, occlusion of the cerebral artery leads to focal ischemia. The ischemic focus is represented by the central zone of necrosis, which is surrounded by an area of the so-called ischemic penumbra, the neurons of which are potentially viable, but the blood supply to this zone remains for a long time at a level below the functional threshold values. Rehabilitation plays a crucial role in improving quality of life in patients after acutevascular brain disorder, as well as their relatives and others. Understandingof legal basis, most modern methods of post-stroke rehabilitation, as well as an understanding of the pathogenesis of neuronal damage and recovery allow to optimize work with these patients. The data accumulated to date indicate that with properly selected timely treatment, the restoration of lost functions after a stroke is not only desirable, but also to a large extent possible. A condition for successful rehabilitation is the use of all available methods of non-drug exposure and drug therapy.